Development of contractor's proposal process model in design-build procurement - Then, Dennis Choo Khun (2005)
Design-build procurement has been dramatically increased recently and has taken over conventional delivery system in both government and private sectors in our construction industry. Despite the advantages of design-build procurement system, there is a great potential for dispute and claim at the construction stage due to the client’s requirement and contractor’s proposal not being well defined at the early stage. Therefore, a process model of dominant contents is developed to guide and assist design-build contractor in preparation of proposal. Essentially, the objectives of this research are to study the concept of design-build system, to study the dominant contents of design-build contractor’s proposal, to identify the degree of importance of the dominant contents and to develop a process model in determining contractor’s proposal in design-build procurement. The scope of the study is only focusing on the typical contents of contractor’s proposal, such as design proposals, financial details, alternative proposals, details on assumptions made, fabrication / construction proposals, contract administration details, details on qualifications / deviations and miscellaneous matters. This study was carried out by going through literature reviews, semi-structured interview and questionnaire survey exercises. The target respondents are developers, architects, contractors, quantity surveyors and design consultants working in the state of Wilayah Persekutuan and Sarawak. Through the process of data collection and analysis, the degrees of importance of the dominant contents have been determined. The results obtained form a basis for the development of a design-build contractor’s proposal process model, by using Data Flow Diagram (DFD) approach. It has been developed to well formulate effective strategies, in order to minimize contractual conflicts and improve project performances in design-build projects.